The - Rogers, Pat (Oxford University Press, 2001)
Britain possesses a literary heritage virtually unrivaled in the Western world. This lavishly illustrated volume explores the richness, diversity, and continuity of that tradition. Under the general editorship of Pat Rogers, some of Britain's foremost literary scholars trace the history of English literature from its first stirrings in Anglo-Saxon poetry to the present day